2008
DOI: 10.1021/es800743p
|View full text |Cite
|
Sign up to set email alerts
|

Environmentally Friendly Slow Release Formulations of Alachlor Based on Clay-Phosphatidylcholine

Abstract: A new clay-liposome complex was developed for reducing leaching of herbicides and contamination of groundwater. The liposomes were composed of the neutral and Environmental Protection Agency approved phospholipid phosphatidylcholine (PC). Adsorption of PC liposomes on the clay mineral montmorillonite could exceed the cation exchange capacity of the clay, and was well simulated by the Langmuir equation. X-ray diffraction results for 6 mM PC and 1.6 g/L clay (3 day incubation) yielded a basal spacing of 7.49 nm,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 21 publications
3
20
0
Order By: Relevance
“…Materials used in agriculture for this purpose include liposomes [4], cyclodextrins [5][6][7], clays [8][9][10], silica [11], lignin [12,13], polymeric microparticles [14][15][16][17][18] and nanoparticles [19,20]. Biodegradable micro and nanoparticles are especially suitable as carriers for pesticides, due to their low toxicity and good biocompatibility.…”
Section: Introductionmentioning
confidence: 99%
“…Materials used in agriculture for this purpose include liposomes [4], cyclodextrins [5][6][7], clays [8][9][10], silica [11], lignin [12,13], polymeric microparticles [14][15][16][17][18] and nanoparticles [19,20]. Biodegradable micro and nanoparticles are especially suitable as carriers for pesticides, due to their low toxicity and good biocompatibility.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, the authors optimised the adsorption of PC on montmorillonite for the preparation of slow‐release herbicide formulations 9. This system proved to be very effective at reducing the leaching of poorly water‐soluble herbicides such as atrazine and alachlor 10.…”
Section: Introductionmentioning
confidence: 99%
“…This provided a binding coefficient for each surfactant, that allowed to predict their sorption for several surfactant/clay ratios. The validity of this approach has been extensively proven for other surfactants [16], [36]. In a second stage, once the amount of sorbing surfactant was determined for particular surfactant/clay ratios, the maximal amount of herbicide which could be sorbed for the employed surfactant concentration was calculated from the solubility studies by considering the same ratio between the solubilized (included in micelles) herbicide and the surfactant in solution as in the formulation with the clay.…”
Section: Resultsmentioning
confidence: 99%
“…It has been previously reported that incorporation of active ingredients in the micelles and vesicles formed by surfactant molecules which adsorbed on clays, such as montmorillonite, provided a slow release system [14][16]. The fraction of the pesticide encapsulated in surfactant-clay complexes prolonged their action.…”
Section: Introductionmentioning
confidence: 99%